Green services and emergence and recovery from the global economic slowdown in developing Asian economies - Mark Stoughton; Anbumozhi Venkatachalam (Asian Development Bank Institute (ADBI), 2010)
The global economic slowdown has again highlighted the vulnerability of export-led development models and economies to downturns in export markets. Economic deepening or rebalancing with an emphasis on service-sector development should be - and is becoming - one long-term response to the crisis by Asia's emerging economies. In the long run, sustainable economic development will depend in part on achieving a green trajectory of service sector development, in which services help green the product economy. In the short run, however, can services help address short- and medium-term challenges of emergence and recovery from the crisis - particularly those of at least resuming historic rates of poverty alleviation and inclusive growth? Meeting these challenges will require that export sectors deal successfully with challenging market conditions. There is a class of closely related business-to-business services which act to green the product economy, and which would improve the competitiveness of export sectors and husband scarce public resources by optimizing the efficiency of infrastructure utilization. These are functional procurement/efficiency services, which transform procurement of environmentally problematic goods and services - such as waste disposal, energy, chemicals, and transport - into performance-based services in which service providers profit by increasing the customer's eco-efficiency. Energy Service Companies (ESCOs) are the best-known of these service models. These services appear to have strong potential among the larger, more sophisticated institutions and commercial and industrial enterprises in developing Asian states, particularly in Asia's more advanced developing economies.
Keywords: L80; L88; O14; O19; O25; 330